A socio-economic impact of Letaba Water Users Association on emerging black farmers at Mopani District Manicipality, Limpopo Province - Ramabulana, Munzhedzi Euphemia (My University, 2007)
Water is a basic need and everybody has a right to have access to it, be it for consumption or irrigation. The principle of rights is applicable in every sphere of life even in the utilization of water resources. South Africa is faced with a problem of water scarcity and deterioration of water resources. The country is in a process of transforming water resource management and has developed different policies and strategies aimed at achieving effective and sustainable utilization of water resources. On the other hand the government has an obligation to meet set national and international targets. The latter can never be achieved without water which is at the center of both economic and social development. The integrated water resource management has been initiated and different institutions have been established i.e. Catchments Management Agencies and Water Users associations. The WUAs are aimed at managing water resources at local level and have been established to replace whites-only Irrigation boards. The National Water Act 36 of 1998 aims at addressing past imbalances provides for WUAs to control, maintain and operate water resources and to ensure equal distribution of water to all users. The act also provides for complete involvement of historically disadvantaged individuals in water resource management processes. The emerging black farmers have been given an opportunity to participate in the WUA activities. The farmers can now utilize water resources equally like other users which has given emerging black farmers an opportunity to engage in farming activities and contribute in the economic growth of the country. Emerging black farmers can farm products which are sold at local, national and international markets. ix Emerging black farmers can now earn a living and improve their standard of living. The farming activities have made it possible for farmers to provide for their families, pay through their children’s education, health services, provide shelter and food security. Farming has created jobs for community members. This research is aimed at assessing the socio-economic impact of LWUA on emerging black farmers of Mariveni and Mavunda farming schemes under Mopani district Municipality in the Limpopo Province. The inclusion of emerging black farmers in LWUA activities has made it possible for them to get water allocation which has made it possible for them to engage themselves in farming activities. The farming activities that the farmers are engaged in have made it possible for the farmers to contribute towards the economy of the country and provide for their families by paying through their children’s education, health services, food and shelter.
Thesis (M. Dev.) -- University of Limpopo, 2007
Keywords: Farmers; Agriculture; Water supply; Water resource development; Farmers; Agriculture; Water supply; Farmers -- economic conditions; Irrigation; Water in agriculture -- South Africa